2017
DOI: 10.1159/000484132
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Oral Lichen Planus with Direct-Acting Antiviral Agents after Liver Transplantation for Hepatitis C Virus-Associated Hepatocellular Carcinoma

Abstract: Hepatitis C virus (HCV) infection is frequently associated with various extrahepatic manifestations, such as autoimmune features and immune complex deposit diseases. Oral lichen planus (OLP) is one such extrahepatic manifestation of HCV infection. Recently, direct-acting antivirals (DAA) have proved to be highly effective and safe for the eradication of HCV. Herein, we report a case of OLP accompanied by HCV-related hepatocellular carcinoma (HCC) that disappeared after liver transplantation and achievement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In contrast to our patients, several cases published in the literature describe patients whose LP improved or resolved after treatment with DAA. 7 , 8 , 9 , 10 , 11 Perhaps the pathogenesis of LP in our patients differs from that of these patients, or perhaps the immunopathogenic drivers of LP in the setting of HCV lag behind treatment or are exacerbated by treatment in some cases. It is also possible our patients' LP was unrelated to HCV or its treatment.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast to our patients, several cases published in the literature describe patients whose LP improved or resolved after treatment with DAA. 7 , 8 , 9 , 10 , 11 Perhaps the pathogenesis of LP in our patients differs from that of these patients, or perhaps the immunopathogenic drivers of LP in the setting of HCV lag behind treatment or are exacerbated by treatment in some cases. It is also possible our patients' LP was unrelated to HCV or its treatment.…”
Section: Discussionmentioning
confidence: 82%
“… 3 However, limited data exist regarding outcomes of HCV-associated skin disease after DAA treatment. Case reports and series have documented HCV-associated cryoglobulinemic vasculitis, 4 porphyria cutanea tarda, 5 and oral and cutaneous LP 6 , 7 , 8 , 9 , 10 improving or resolving after DAA treatment. Conversely, new-onset LP developing 3 months after HCV treatment with elbasvir-grazoprevir was recently described, 11 and a patient with pre-existing oral LP who had new cutaneous LP after treatment with ledipasvir-sofosbuvir was also reported.…”
mentioning
confidence: 99%
“…We showed that, of patients with OLP, 62% had HCV antibodies and 60% had HCV RNA in their serum [11]. Furthermore, there is evidence that treatment with DAAs improves OLP associated with HCV-related infection [12][13][14][15].…”
Section: Ehime Prefecturementioning
confidence: 80%
“…They reported that HCV eradication after DAA therapy involves immune reconstitution[50]. These immune reconstitutions may support the successful treatment of oral lichen planus after DAA therapy[51]. Thus, rapid immunological changes, including in NKG2D systems are observed during and after DAA treatment, and they may have several effects on HCC occurrence and recurrence.…”
Section: Immunological Mechanisms Of Hcc Occurrence and Recurrence Afmentioning
confidence: 99%